Community REACH: An Implementation of an Evidence-Based Caregiver Program. (19th March 2018) - Czaja, Sara J; Lee, Chin Chin; Perdomo, Dolores; Loewenstein, David; Bravo, Marina; Moxley, PhD, Jerad H; Schulz, Richard
Abstract: Background and Objectives: Family caregivers (CGs) are critical to the provision of long-term services and support for older adults. Numerous intervention programs to alleviate CG distress have been developed and evaluated yet few have been implemented in community settings. This paper describes and presents outcomes from Community REACH, a community implementation of the evidence-based Resources for Enhancing Alzheimer's Caregiver Health (REACH) II program. Research Design and Methods: Community REACH involved a partnership between REACH II investigators and United HomeCare Services (UHCS), a nonprofit home health organization that provides home health, personal care, companion, and respite services. The intervention program, an adapted version of an evidence-based program, was a 6-month multicomponent psychosocial intervention, which involved six individual face-to-face and six individual telephone sessions, and telephone support groups. One hundred and forty-six CGs who were primarily female (76%) and Latino, and providing care for an individual with Alzheimer's disease (AD) were enrolled. Program effectiveness was assessed by examining changes in perceived social support, burden, and depression, and CG self-efficacy. Results: At 6 months, CGs reported significant decreases in depression, burden, being and bothered by the care recipient's memory problems. There was also a significant decline in the number of CGs at risk for clinical depression. These improvements were maintained at 12 months and there was an increase in feelings of social support. Discussion and Implications: The findings indicate that evidence-based CG programs can be successfully implemented in community settings and benefit CGs of AD patients. A continued partnership between the program developers and community partners is key to implementation success.